Impact of COVID-19 disease on obstetric outcomes in the third trimester of pregnancy - Karaşin, Süleyman Serkan; Bayram, Feyza (The European Research Journal, 2023)
Objectives: The aim of this study is to evaluate the effect of coronavirus disease 2019 (COVID-19) diagnosed in the third trimester of pregnancy on maternal, fetal, and obstetric outcomes. Methods: This retrospective study included 109 pregnant women hospitalized with a diagnosis of COVID-19 during the third trimester of pregnancy (28-40 weeks) in a tertiary center between March 1 and December 31, 2020. Demographic characteristics, clinical signs, and obstetric outcomes of the patients were searched for analysis. Laboratory and x-ray results were reported, and treatment methods were summarized. Finally, mother-newborn results were recorded. Results: We included one hundred nine pregnant women in this study. We divided the patients into two groups as those with positive PCR test (n = 59) and negative PCR test and possible covid patients (n = 50) whose symptoms and histories meet the covid criteria. The mean age of the patients was 28.90 ± 6.21 years, and the mean week of gestation was 37.45 ± 2.29 weeks. Half of the patients were asymptomatic (n = 57, 47.7%), and 69% of all patients were delivered by cesarean section. The hospitalization time of antigen-positive cases was between 2-9 days. The mean lymphocyte count was 1.37 ± 0.45 ×103/mL in the PCR positive patient group, and this value was 1.67 ± 0.54 103/mL in the PCR negative patients (p = 0.007). While the mean neutrophil count was 8.13±3.16 ×103/mL in the PCR positive patient group, this value was 10.99 ± 4.14 ×103/mL in the PCR negative patients (p < 0.001). Fifteen patients required intensive care unit follow-up, and 2 of them died while receiving mechanical ventilator support. Conclusions: COVID-19 infection in the third trimester of pregnancy does not affect fetal and maternal outcomes if the disease is under control at an early stage. In hospitalized patients, symptoms are more precious than antigen testing.